2010
DOI: 10.1063/1.3364861
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational multiconfiguration self-consistent field theory: Implementation and test calculations

Abstract: A state-specific vibrational multiconfiguration self-consistent field (VMCSCF) approach based on a multimode expansion of the potential energy surface is presented for the accurate calculation of anharmonic vibrational spectra. As a special case of this general approach vibrational complete active space self-consistent field calculations will be discussed. The latter method shows better convergence than the general VMCSCF approach and must be considered the preferred choice within the multiconfigurational fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 53 publications
(26 reference statements)
0
65
0
Order By: Relevance
“…[29,33,52] Subspace iteration methods for vibrational problems have been used before in the context of molecular mechanics applications, [53][54][55][56] where huge Hessians must be diagonalized and where subspace iteration techniques are a natural means to solve the diagonalization problem. In quantum chemistry, however, the Mode-Tracking idea established new principles [28,[57][58][59][60][61][62][63] : (1) isolated, structure-characteristic vibrations can be directly targeted, (2) vibrations that involve only a subset of atoms (e.g., in the case of adsorbates on surfaces [64] or in quantum mechanics (QM)/molecular mechanics (MM) partitionings [65] ) can be directly optimized, (3) low-dimensional Hessians also benefit if their entries are time-consuming to calculate. In our former work, [51] it was shown that the proper construction of a guess vector has an important influence on the convergence characteristics of the algorithm.…”
Section: Mode-trackingmentioning
confidence: 99%
See 1 more Smart Citation
“…[29,33,52] Subspace iteration methods for vibrational problems have been used before in the context of molecular mechanics applications, [53][54][55][56] where huge Hessians must be diagonalized and where subspace iteration techniques are a natural means to solve the diagonalization problem. In quantum chemistry, however, the Mode-Tracking idea established new principles [28,[57][58][59][60][61][62][63] : (1) isolated, structure-characteristic vibrations can be directly targeted, (2) vibrations that involve only a subset of atoms (e.g., in the case of adsorbates on surfaces [64] or in quantum mechanics (QM)/molecular mechanics (MM) partitionings [65] ) can be directly optimized, (3) low-dimensional Hessians also benefit if their entries are time-consuming to calculate. In our former work, [51] it was shown that the proper construction of a guess vector has an important influence on the convergence characteristics of the algorithm.…”
Section: Mode-trackingmentioning
confidence: 99%
“…The subscript ' 'eq' ' indicates that the second derivative has to be taken at an equilibirum geometry, that is at a stationary point on the potential energy surface. More accurate methods for the variational calculation of molecular vibrations including anharmonic effects [2][3][4][5][6][7] are under constant development but can hardly be applied to truly large molecules containing on the order of 100 atoms and more. Hence, molecular dynamics approaches are often used as a means to include anharmonic effects on the motion of atomic nuclei [8,9] but suffer from the neglect of quantum effects on the nuclear motion.…”
Section: Introductionmentioning
confidence: 99%
“…This situation corresponds to static electron correlation effects as any kind of resonance cannot be described by the VSCF approach and thus the VSCF wave function is qualitatively incorrect. For that reason Culot and Lievin 89,90 developed the vibrational multiconfiguration self-consistent field approach, VMCSCF, which can be considered the static variant of the multi-configuration time-dependent Hartree method, MCTDH, of Meyer et al 91−93 Quite recently we presented a novel and efficient implementation of VMCSCF theory 34,35 based on Jacobi 2×2 rotations as originally proposed by Hinze for electronic wave functions.    ˆ, ...…”
Section: B Multi-configuration Self-consistent Field Theorymentioning
confidence: 99%
“…For further details see Ref. 34. Consequently, these equations can be solved by consecutive Jacobi rotations for each mode (microiterations).…”
Section: B Multi-configuration Self-consistent Field Theorymentioning
confidence: 99%
See 1 more Smart Citation